Systems Engineering and Its Application to Industrial Product Development - Brusa, Eugenio; Calà, Ambra; Ferretto, Davide; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Mastering the complexity of innovative systems is a challenging aspect of design and product development. Only a systematic approach can help to embed an increasing degree of smartness in devices and machines, allowing them to adapt to variable conditions or harsh environments. At the same time, customer needs have to be identified before they can be translated into consistent technical requirements. The field of Systems Engineering provides a method, a process, suitable tools and languages to cope with the complexity of various systems such as motor vehicles, robots, railways systems, aircraft and spacecraft, smart manufacturing systems, microsystems, and bio-inspired devices. It makes it possible to trace the entire product lifecycle, by ensuring that requirements are matched to system functions, and functions are matched to components and subsystems, down to the level of assembled parts. This book discusses how Systems Engineering can be suitably deployed and how its benefits are currently being exploited by Product Lifecycle Management. It investigates the fundamentals of Model Based Systems Engineering (MBSE) through a general introduction to this topic and provides two examples of real systems, helping readers understand how these tools are used. The first, which involves the mechatronics of industrial systems, serves to reinforce the main content of the book, while the second describes an industrial implementation of the MBSE tools in the context of developing the on-board systems of a commercial aircraft.
Introduction -- The Systems Engineering -- The Methodology of Systems Engineering -- Systems, Customer Needs and Requirements -- Operational Analysis.
Keywords: Mechatronics; Manufactures; Engineering design; Dynamics; Nonlinear theories; Mechatronics; Machines, Tools, Processes; Engineering Design; Applied Dynamical Systems